An Exploratory Study on The Relationship of Public Governance and Ease of Doing Business - Sofik Handoyo (APMBA (Asia Pacific Management and Business Application), 2017)
This study aims to investigate the relationship of good public governance and ease of doing a business performance. The motivation of the study was driven by slowing down global economy and competition among countries around the world to attract Foreign Direct Investment (FDI). Foreign investors will consider investing their capital in a certain country if in that country adopting ease of doing business practice. The study was intended to reveal, whether the country that applies the good practice of public governance will also lead to good performance in terms of ease of doing business. The study adopted exploratory research design which is public governance and ease of doing business performance treated as two independent variables. Public governance variable was represented by attributes namely public accountability, effectiveness government, regulatory quality, control of corruption, rule of law and political stability. World Governance Index (WGI) was adopted to measure Public Governance and Distance to Frontier (DtF) value is representing a measurement of ease of doing a business performance. The study applied bivariate correlation analysis and involved 188 countries member of World Bank. The results showed that all public governance attributes were positively and significantly associated with ease of doing a business performance. Pearson correlation coefficient indicated that all attributes of public governance had a strong correlation ( r  > 0.6, p<0.01), except for political stability attribute (r = 0.584, p<0.01).  The result implies that practice of good public governance in governmental institution have potential impact on performance of the government in terms of streamlining bureaucracy of doing business in that country.